Fetal malformations: temporal distribution and its association with the use of pesticides in Rio Grande do Sul - Donat, Milena Makoski (2023)
The aim of this study is to examine the temporal distribution of congenital malformation rates in Rio  Grande do Sul and its potential correlation with  pesticide use. This quantitative research adopts an exploratory descriptive approach and was conducted  in the first half of 2022. The association between  malformation occurrences and pesticide use was  determined using Odds Ratios, with a 95% Confidence Interval (CI) applied to the sample. The study reveals  variations in congenital malformation rates across the  five analyzed periods. The findings suggest a likely  association between malformation occurrences in Rio  Grande do Sul and pesticide use. Notably, all annual  percentage variation values were statistically  significant, with positive values indicating an annual  increase in congenital malformation incidences in the  region. Moreover, the study highlights the presence  of variability in the reported cases of all  malformations examined throughout the analyzed  period. This research underscores the importance of  preventing exposure to pesticides, as their widespread and inappropriate usage is linked to detrimental  effects on human health. Safeguarding against such  exposure becomes crucial in mitigating the risks  associated with congenital malformations.